Encouraging Landscape Water-Conservation Behaviors: Applying Audience Segmentation to Water Conservation Activities in the Landscape—Defining Segments of the Florida Homeowner Audience and Implications for Extension Programming - Laura A. Warner; Emmett Martin; Alexa J. Lamm; Joy N. Rumble; Esen Momol (EDIS)
This is the second publication in the Encouraging Landscape Water Conservation Behaviors series, which focuses on encouraging water conservation among Florida residents who use irrigation in their home landscapes. This 6-page fact sheet examines one approach to segmenting Florida residents who use irrigation in the home landscape. It also describes how segmentation can be used to encourage water conservation practices. Written by Laura A. Warner, Emmett Martin, Alexa J. Lamm, Joy N. Rumble, and Esen Momol, and published by the Department of Agricultural Education and Communication, May 2016.